Awareness about adverse drug reaction monitoring and pharmacovigilance among final year medical students in tertiary care teaching hospital in Andhra Pradesh: a cross sectional study - Rao, A. P. Narasimha; Lakshmi, S. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Adverse drug reaction (ADR) is an unwanted, undesirable effect of a drug that occurs during clinical use. ADRs will occur daily in health care institutions and can unfavourably affect a patient’s quality of life, frequently causing considerable morbidity and mortality. Pharmacovigilance is defined as the science and activities relating to the detection, assessment, understanding and prevention of adverse effects or any other drug-related problem. Methods: It was a non-interventional study was done among hundred final year medical students at Kurnool Medical College, Kurnool, Andhra Pradesh. The study instrument was a predesigned questionnaire was structured by following the precedence, which was set by parallel studies. The participants were given forty-five minutes to answer the questionnaire; the questionnaires were then analyzed by grading the respondents into three categories: poor, unsatisfactory and satisfactory. Results: This study showed satisfactory results about awareness, knowledge and methods of application of pharmacovigilance among final year medical students 55%, 47%, 54% respectively and positive correlation between awareness, knowledge and methods of application of pharmacovigilance among final year medical students significantly (<0.0001) correlated. Conclusions: The present study revealed that the final year medical students were satisfactory in awareness and knowledge and methods of application of pharmacovigilance. The correlations told that the higher the awareness, the more was the knowledge and better were the methods of application. Likewise, the knowledge and practices were significantly and positively related to a correlation.